A study of new fixed point results via hybrid contractions - Mohammed Shehu Shagari; Paul Oloche (Journal of Mahani Mathematical Research)
The available literature shows that the ideas of admissible mappings and that of Suzuki-type contractions on metric spaces have been well-investigated. However, a hybrid version of these results in connection with $θ$-contraction has not been adequately examined. On this basis therefore, the aim of this paper is to introduce a new concept under the name an admissible Jaggi-Suzuki-type hybrid ($θ$-$φ$)-contraction and to study new conditions for the existence of fixed point for this class of contractions on generalized or rectangular metric space. Applications and examples are provided to support the assumptions of our presented theorems. The results established herein extend some existing ideas in the corresponding literature. A few of these special cases are highlighted and discussed as corollaries.